Determinación de la frecuencia de parásitos gastrointestinales y pulmonares, en tres veredas del municipio de Toribío-Cauca - Hurtado Maya, Marjoleine Patricia; Noreña Mestizo, Fernanda; Ulchur Montano, Álvaro Javier (Universidad Antonio Nariño, 2022)
The present study on the determination of the frequency of gastrointestinal and pulmonary parasites in three villages in the municipality of Toribio - Cauca was carried out during the second semester of 2021 in the Tacueyó shelter, villages López, Santo Domingo and Agua Blanca in the municipality of Toribio, at northeast of the department of Cauca, Colombia in 100 bovines between males and females of different sex, age and race. Fecal matter samples were taken and analyzed in the Parasitology laboratories and the laboratory by means of flotation tests, with a Mac master camera and Baermann's test. Of the 100 samples analyzed in the three villages, 31% were positive for Trichostrongylus, 2% for Trichostrongylus and Coccidia, and 67% negative. Of the total number of animals sampled (100), 67% were female and 33% male; Of the females, 29 (43.28%) were infested with Trichostrongylus and Coccidia, and of the males, 4 (12.12%) were infested with Trichostrongylus. The presence of Dictyocaulus was not detected in any of the farms. In general, the frequency was low, which indicates that the deworming plans implemented on the farms have had a positive impact; however, it is essential to establish deworming plans or controls in the cattle herds, to train and raise awareness among small and medium farmers regarding the management and use of dewormers, and to carry out complementary diagnostic tests. Finally, it is of great significance to maintain in optimal conditions the places where the animals frequent, since in many occasions it is from these elements where many problems of parasitosis can be generated in the animals.